The phenomenon of queer strategy in female rock poetry of the 1990s (Based on the poetic texts by Diana Arbenina and Svetlana Surganova) - A.S. Afanasev (Ученые записки Казанского университета: Серия Гуманитарные науки)
This paper is devoted to the analysis of ways of artistic representation of the queer strategy, which was relevant in the female rock culture of the 1990s. At first, the strategy worked primarily for the benefit of the image of performers. Later, it promoted their cultural codification. The relevance of the study is due to the great interest of the humanities in gender issues, particularly, in the gender analysis of the text. The study has been performed in order to identify the main forms of explication of the queer strategy in female rock culture. To fulfill this purpose, the following main methods have been used: structural, motivational, and biographical. The paper cites a series of examples proving that this strategy was used in the most declarative and consistent way by the duet “Nochnye Snaipery” ('Night Snipers') by Diana Arbenina and Svetlana Surganova. The duet was perceived as a queer due to the biographical myth that was created by both the musicians themselves and their fans. Simulation of the queer image took place at two levels: visual (appearance, style of dress, behavior) and verbal (lyrics). The material for the literary analysis is the first album of the duet “Kaplya degtya v lozhke meda” ('A Drop of Tar in a Spoon of Honey') (1998), the authentic version of which included 27 compositions. Based on the results of the study, the following conclusions have been made: the queer strategy in the verbal subtexts of the rock composition is realized through the “floating” gender identity of the lyric subject and object and the poetics of corporeality. The obtained results are of great importance for further research of the gender image of the world in female rock poetry.